2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC) 2015
DOI: 10.1109/pvsc.2015.7355708
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stress durability testing to better predict outdoor performance of PV modules

Abstract: Photovoltaic modules in the outdoor environment are subjected to a wide range of stresses which can operate simultaneously and sequentially and can vary based on climate and installation.These stresses can include temperature, temperature variation, localized heating, humidity, moisture (rain, snow, humidity, condensation), weathering, mechanical stress, abrasion and internal electric fields. These multiple stress make prediction of service lifetime challenging. Frequently resistance to an extended single stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Backsheets based on PVF and PET have been used for more than 30 years and have served as good standards for performance and durability in PV applications. Field studies have confirmed its outstanding long-term performance relative to other backsheet materials [106,129].…”
Section: Lessons Learned From New Degradation Modes Explained By the ...mentioning
confidence: 86%
See 3 more Smart Citations
“…Backsheets based on PVF and PET have been used for more than 30 years and have served as good standards for performance and durability in PV applications. Field studies have confirmed its outstanding long-term performance relative to other backsheet materials [106,129].…”
Section: Lessons Learned From New Degradation Modes Explained By the ...mentioning
confidence: 86%
“…Several 'extended testing' procedures were proposed from different test houses, manufacturers, reinsurance and engineering companies, see e.g. [105], DuPont [106] and the Product qualification Program of PVEL [107] having both eight parallel test sequences, but different ones.…”
Section: Impact On Module Testing Procedures and Standardizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, glass is difficult to deteriorate due to UV and hygrothermal stress unlike normal PET. 9,10) And A lower water vapor transmission rate than the normal type backsheet prevent acetic acid from producing. 11,12) Figures 5-7 show the result of a 5400 Pa mechanical load test after 3000 h of damp heat test (DH), a thermal cycle test (TC) of 600 cycles, and combination test repeated three times that involved a thermal cycle test and humidity freeze test (HF).…”
Section: Reliability Testsmentioning
confidence: 99%